Analisa Sistem Dan Prosedur Pengelolaan Keuangan Kecamatan Tarogong Kaler - Irma Rosmayati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research to find out about the procedures and steps in implementing financial management systems and procedures in government institutions, in this case the Tarogong Kaler District office, Garut Regency. As a government institution, of course it is required to create financial management that is accountable, transparent and of course effective and efficient, so that it can account for everything to the relevant parties and society in general. In this research the author used a descriptive qualitative research method by paying attention to the results of interviews and reviewing related data obtained from several accurate resources.